Enhancing sustainability and key success factors in digital food supply chain management through digital transformation: A fuzzy AHP approach - Wiwatkajornsak, Sirorat; Phuaksaman, Chayathach (Engineering and Applied Science Research, 2025)
This study investigated the key success factors in digital food supply chain management for Thailand's food retail industry through digital transformation, employing the Fuzzy Analytic Hierarchy Process (FAHP) for the integrated digital food supply chain model. Through an extensive literature review and expert consultations, the critical criteria were identified and ranked in the researched domains of digital strategy, digital operations management, digital customer experiences, and digital organization and culture management. Business alignment is the primary focus within digital strategy, followed by technology investments to enable this alignment and data-driven decision-making. Supply chain visibility is considered the most crucial aspect of digital operations management, and data analytics along with inventory management are integral aspects that lead to operational efficiency. In the realm of digital customer experiences, aspects of customer centricity, convenience and accessibility, and order tracking and communication are the top drivers of satisfaction and loyalty. Finally, leadership and vision are recognized as essential for digital organization and culture management, along with fostering digital skills, capabilities, agility, and adaptability. In addition, this study provides a practical framework for improving Thai food retail organizations through the alignment of engineering, organizational, and consumer expectations.